Complex Systems Design &Amp; Management 2014
DOI: 10.1007/978-3-319-02812-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Variability in Model Based Systems Engineering

Abstract: Automotive model-based systems engineering needs to be adapted to the industry specific needs, in particular by implementing appropriate means of representing and operating with variability. We rely on existing modeling techniques as an opportunity to provide a description of variability adapted to a systems engineering model. However, we also need to take into account requirements related to backwards compatibility with current practices, given the industry experience in mass customization. We propose to adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
12
0
3
Order By: Relevance
“…In fact, if variability models are written in an intermediate language, such as HLVL, they could be integrated analyzed and configured into a single model in an integrated way. This research gives continuity to previous works [8,17,19,24] that exploit the idea of relying on a variability language that unifies existing notations to provide genericity to the methods, techniques, and tools used for modeling, analysis, and configuration. Section 2 the ontological approach used to design HLVL.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In fact, if variability models are written in an intermediate language, such as HLVL, they could be integrated analyzed and configured into a single model in an integrated way. This research gives continuity to previous works [8,17,19,24] that exploit the idea of relying on a variability language that unifies existing notations to provide genericity to the methods, techniques, and tools used for modeling, analysis, and configuration. Section 2 the ontological approach used to design HLVL.…”
Section: Introductionmentioning
confidence: 70%
“…More particularly, the conceptualization included languages that (1) have been transformed to logic or constraint programming to automate analysis tasks; and (2) their semantics is formally defined, and were included in other conceptualization studies. Hence, this step included feature-oriented languages [5,13,14,26]; variation point oriented languages [8,12,20,22,23]; and decision-oriented languages [4,6,7,25]. Finally, the review included proposals introducing constructs for modeling complex variability relations, such as conditional and quantified constraints [8,14,21].…”
Section: Designing Hlvl Following An Ontological Approachmentioning
confidence: 99%
“…Product Line Engineering can be applied to Embedded RTS development to reduce the costs and schedules [33]. Requirement engineering is critical for Embedded Real-Time Systems, as a good requirement plan leads to less changes and risks being identified during the implementation stage.…”
Section: Discussionmentioning
confidence: 99%
“…As the paper by C. Dumitrescu et al [33] suggests, variability should be compatible with legacy documents. Using the integrated variability documentation method requires changing the complexity of development artefacts by introducing both commonality and variability into existing models [9].…”
Section: B Integrated Variability Documentationmentioning
confidence: 99%
“…Dumitrescu et al [11,12] reported on their experience in an automotive model based systems engineering. Mussbacher et al [21] propose an extension of the Aspect-oriented User Requirements Notation (AoURN) to support variability modeling.…”
Section: Comparison With Existing Solutionsmentioning
confidence: 99%